Acute effect of citrulline malate on repetition performance during strength training: A systematic review and meta-analysis - Tonstad Vårvik, F.; Bjørnsen, T.; Gonzalez, A. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
Citrulline malate (CitMal) is a dietary supplement that is suggested to enhance strength training performance. However, there is conflicting evidence on this matter. Thus, the purpose of this meta-analysis was to determine whether supplementing with CitMal prior to strength training could increase the total number of repetitions performed before reaching voluntary muscular failure. A systematic search was conducted wherein the inclusion criteria were double-blind, placebo-controlled studies in healthy participants that examined the effect of CitMal on repetitions to failure during upper body and lower body resistance exercises. The Hedges`s g standardized mean differences (SMD) between the placebo and CitMal trials were calculated and used in a random effect model. Two separate subanalyses were performed for upper body and lower body exercises. Eight studies, including 137 participants who consisted of strength-trained men (n = 101) and women (n = 26) in addition to untrained men (n = 9), fulfilled the inclusion criteria. Across the studies, 14 single-joint and multijoint exercises were performed with an average of 51 ± 23 total repetitions during 5 ± 3 sets per exercise at ~70% of one-repetition maximum. Supplementing with 6-8 g of CitMal 40-60 min before exercise increased repetitions by 3 ± 5 (6.4 ± 7.9%) compared with placebo (p = .022) with a small SMD (0.196). The subanalysis for the lower body resulted in a tendency for an effect of the supplement (8.1 ± 8.4%, SMD: 0.27, p = .051) with no significant effect for the upper body (5.7 ± 8.4%, SMD: 0.16, p = .131). The current analysis observed a small ergogenic effect of CitMal compared with placebo. Acute CitMal supplementation may, therefore, delay fatigue and enhance muscle endurance during high-intensity strength training.